2021
DOI: 10.1108/ijoem-11-2020-1348
|View full text |Cite
|
Sign up to set email alerts
|

Investigating efficiency of frontier stock markets using multifractal detrended fluctuation analysis

Abstract: PurposeThe investigation of the fractal nature of financial data has been growing in the literature. The purpose is to investigate the multifractal behavior of frontier markets using multifractal detrended fluctuation analysis (MFDFA).Design/methodology/approachThis study used daily closing prices of nine frontier stock markets up to 31-Aug-2020. A preliminary analysis reveals that these markets exhibit fat tails and clustering patterns. For a more robust analysis, a combination of Seasonal and Trend Decomposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…However, some scholars have studied the effectiveness of financial market is anti-persistent. For example, Aslam et al (2021) found that markets in Kenya, Morocco, Romania, and Serbia exhibit anti-persistent behavior when studying the efficiency of frontier markets. Diao et al ( 2020) explored the efficiency of the five ASEAN countries' markets and found that the Chinese market has anti-persistent and so on.…”
Section: Time-varying Hurst Index Analysismentioning
confidence: 99%
“…However, some scholars have studied the effectiveness of financial market is anti-persistent. For example, Aslam et al (2021) found that markets in Kenya, Morocco, Romania, and Serbia exhibit anti-persistent behavior when studying the efficiency of frontier markets. Diao et al ( 2020) explored the efficiency of the five ASEAN countries' markets and found that the Chinese market has anti-persistent and so on.…”
Section: Time-varying Hurst Index Analysismentioning
confidence: 99%
“…Later, an extension of the DFA, i.e., multifractal detrended fluctuation analysis (MFDFA) by Kantelhardt, et al [74] was derived, and this has been employed to examine the multifractality of various financial time series such as crude oil [75], stock markets [76][77][78], cryptocurrencies [79], and even sin markets [80]. Meanwhile, based on the concept of the DFA, Podobnik, et al [81] developed the detrended cross-correlation analysis (DCCA) to examine the long-range cross-correlations between two non-stationary time series, which has been applied to various analyses [82,83].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, this study aims to investigate asymmetric MF in leading Middle East and North Africa (MENA) stock markets. Previously most of the studies focus on the symmetric MF analysis of markets by assuming similar reactions of market participants in bearish and bullish market conditions (Aslam et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, this study aims to investigate asymmetric MF in leading Middle East and North Africa (MENA) stock markets. Previously most of the studies focus on the symmetric MF analysis of markets by assuming similar reactions of market participants in bearish and bullish market conditions (Aslam et al, 2021). However, market participants behave differently during the upward and downward market conditions (Cao et al, 2013;Shahzad et al, 2020;Mensi et al, 2021a, b), which motivate us to do asymmetric multifractality (A-MF) analysis rather than focussing on aggregate behaviour based symmetric MF analysis.…”
Section: Introductionmentioning
confidence: 99%